IB - Drucker, Peter F. (London, 1985)
Peter Drucker has organized his book into three main parts or aspects of innovation and entrepreneurship: Practice of Innovation (including the sources, i.e. unexpected; industry and market structure; demographics; changes in perception; new knowledge; the bright idea); Practice of Entrepreneurship (entrepreneurial management; the entrepreneurial business; entrepreneurship in the service institution; the new venture); Entrepreneurial Strategies (ecological niches: changing values and characteristics). The book presents innovation and entrepreneurship as a practice and a discipline using the actions and behaviour of entrepreneurs to exemplify a point, a rule or warning, Innovation and entrepreneurship is represented as essentially purposeful, a task to be organized and as systematic work.
Keywords: Enterpreneur